2015
DOI: 10.1016/j.soildyn.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Newmark sliding block model for pile-reinforced slopes under earthquake loading

Abstract: Re: Submission of revised manuscript for publication in Soil Dynamics and Earthquake Engineering: "Newmark sliding block model for pile-reinforced slopes under earthquake loading" (Revision 2) My co-author and I hereby submit the above named revised manuscript for publication in Soil Dynamics and Earthquake Engineering as a full technical paper. We have included a full response to the reviewers' additional minor comments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…This can be interpreted as a result of the rapid mobilisation of root-soil interaction due to the initial soil slip under dynamic loading. Al-Defae & Knappett (2015) have demonstrated that, for the case of large vertical piles reinforcing slopes to significant depths, the full lateral restraint of the piles is mobilised within 2% of the pile diameter; applying this analogously to the root analogues here would suggest very rapid mobilisation due to the small root diameters. After the first two motions, relatively smaller reductions (in total 14%) were observed, which indicates that the additional resistive force of the root is largely constant after the initial rapid increase.…”
Section: (B)mentioning
confidence: 74%
“…This can be interpreted as a result of the rapid mobilisation of root-soil interaction due to the initial soil slip under dynamic loading. Al-Defae & Knappett (2015) have demonstrated that, for the case of large vertical piles reinforcing slopes to significant depths, the full lateral restraint of the piles is mobilised within 2% of the pile diameter; applying this analogously to the root analogues here would suggest very rapid mobilisation due to the small root diameters. After the first two motions, relatively smaller reductions (in total 14%) were observed, which indicates that the additional resistive force of the root is largely constant after the initial rapid increase.…”
Section: (B)mentioning
confidence: 74%
“…Here, non-associative flow was modelled by adjusting the value of ' = ' mob used in the analyses from the actual value for the true non-associative behaviour to an equivalent associative value   as suggested in [20] and previously used for other seismic limit analysis problems (e.g. [21], [22]), given by:…”
Section: Influence Of Non-associativitymentioning
confidence: 99%
“…When a ground motion is large enough to push the mobilised yield surface to the capping yield surface the soil will dilate to the maximum (capping) condition and any further increase in ground acceleration and seismically induced shear stress will not further change the shape of yield surface. Compared to recent previous sliding block models ([13], [22]) which considered strong ground motions with peak accelerations large enough to easily exceed the peak strength, the use of ' mob here extends the range of applicability to smaller ground motions, a feature which will be useful in the later validation against centrifuge data.…”
Section: Mobilised Friction Angle Accounting For Pre-peak Deformationsmentioning
confidence: 99%
“…Kumar A. [9], Luo C. [10] and Al-Defae A. H. [11] perform a study on seismic performance of pile foundation, finding that the bridge seismic performance not only touches upon bridge structure but it relates to boundary condition. Since dynamic is a key matter for bridge seismic research, the river bed scour weakens seismic capacity of pile foundation and changes structural dynamic performance as well, consequently further swaying seismic response.…”
Section: Introductionmentioning
confidence: 99%